A Cost-Effectiveness Analysis of Rooming-in and Breastfeeding in Neonatal Opioid Withdrawal - Avram, Carmen M.; Yieh, Leah; Dukhovny, Dmitry; Caughey, Aaron B. (American Journal of Perinatology, 2020)
Objective Our cost-effectiveness analysis investigated rooming-in versus not rooming-in to determine optimal management of neonates with neonatal opioid withdrawal (NOW).Study Design A decision-analytic model was constructed using TreeAge to compare rooming-in versus not rooming-in in a theoretical cohort of 23,200 newborns, the estimated annual number affected by NOW in the United States. Additional considerations included the effect of breast milk versus formula milk in evaluating the need for pharmacotherapy. Primary outcomes were needed for pharmacotherapy and neurodevelopment. We assumed a societal perspective in evaluating costs and maternal-neonatal quality-adjusted life years (QALYs) using a willingness-to-pay threshold of $100,000/QALY. Model inputs were derived from literature and varied in sensitivity analyses.Results Rooming-in resulted in fewer neonates requiring pharmacotherapy when compared with not rooming-in. The rooming-in group had more neonates with intact/mild neurodevelopmental impairment and fewer cases of moderate to severe impairment. Rooming-in resulted in cost savings of $509,652,728 and 12,333 additional QALYs per annual cohort. When the risk ratio of need for pharmacotherapy in rooming-in was varied across a clinically plausible range, rooming-in remained the cost-effective strategy.Conclusion Maternal rooming-in with newborns affected by NOW leads to reduced costs and increased effectiveness. Management strategies should optimize nonpharmacological interventions as first-line treatment.
Keywords: breastfeeding; opioid; rooming-in; withdrawal